Causal implementation of rate-independent linear damping for the seismic protection of low-frequency structures. (January 2022) - Liu, Wei; Ikago, Kohju
Abstract: Damage to low-frequency structures caused by recent major earthquakes, such as the 2011 Great East Japan Earthquake, have emphasized the need to protect these structures from low-frequency ground motions. Previous studies have suggested that rate-independent linear damping (RILD) is a viable option for simultaneously reducing excessive displacement and floor response accelerations of low-frequency structures. The majority of previous studies on RILD have focused on the theoretical and mathematical aspects, while the physical implementation of RILD has not yet been extensively investigated. Therefore, this study proposes a novel method based on using a digital filter for causally and physically implementing RILD and examines its feasibility for the protection of low-frequency structures. A feasibility study based on a numerical analysis is conducted to identify the limitations of the proposed method.